Penderitaan Penduduk Palestina dalam Cerita Pendek Al-Qamish Al-Masruq karya Ghassan Kanafani Analisis Sosiologi Sastra Ian Watt - Izazi, Amar; Nashiruddin, Muhammad (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
Abstract This research aims to determine the portrait of the suffering of the Palestinian population in the short story Al-Qamish Al-Masruq by Ghassan Kanafani. The theme raised in this short story is about the situation of the Palestinian population in exile after being expelled by Israel. This is in accordance with the principle of literary works which function as a reflection of the condition of society. The research method used is a qualitative descriptive method. Meanwhile, the approach to this research is the literary sociology approach by Ian Watt.. Analysis of the short story text Al-Qamish Al-Masruq with this approach uses three objects or three factors: The relationship between the author of the work and his community, the literary work itself, the function of the literary work in society's life. The results of the analysis of the short story Al-Qamish Al-Masruq are that there are three forms of suffering of the Palestinian population in displacement: (1) Hunger (2) Poverty (3) Exploitation (4) Social gap Key words: Palestine, suffering, Al-Qamish Al-Masruq, sociology of literature, Arabic literature Abstrak Penelitian ini bertujuan untuk mengetahui potret penderitaan penduduk Palestina dalam cerita pendek Al-Qamish Al-Masruq karya Ghassan Kanafani. Tema yang diangkat dalam cerita pendek ini adalah tentang keadaan penduduk Palestina dalam pengasingan setelah terusir oleh Israel. Hal ini sesuai dengan prinsip karya sastra yang berfungsi sebagai cerminan kondisi masyarakat. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Sedangkan pendekatan untuk penelitian ini adalah pendekatan sosiologi sastra oleh Ian Watt.. Analisis teks cerita pendek Al-Qamish Al-Masruq dengan pendekatan ini melalui tiga objek atau tiga faktor : Hubungan penulis karya dengan masyarakatnya, karya sastra itu sendiri, fungsi karya sastra terhadap kehidupan masyarakat. Hasil dari analisis cerita pendek Al-Qamish Al-Masruq adalah ada tiga bentuk penderitaan penduduk Palestina dalam pengungsian : (1) Kelaparan (2) Kemiskinan (3) Eskploitasi . (4) Kesenjangan sosial Kata kunci : Palestina, penderitaan, Al-Qamish Al-Masruq, sosiologi sastra, sastra Arab